The Jobless Future : Second Edition - Aronowitz, Stanley (Book collections on Project MUSE., 2010)
High technology will destroy more jobs than it creates . This grim prediction was first published in the 1994 edition of The Jobless Future, an eerily accurate title that could have been written for today's dismal economic climate. Fully updated and with a new introduction by Stanley Aronowitz and William DiFazio, The Jobless Future warns that jobs as we know them-long-term, with benefits-are an endangered species.